Enhancing rice ecological production: synergistic effects of wheat-straw decomposition and microbial agents on soil health and yield - Wen, Yanfang; Ma, Yangming; Wu, Ziniu; Yang, Yonggang; Yuan, Xiaojuan; Chen, Kairui; Luo, Yongheng; He, Ziting; Huang, Xinhai; Deng, Pengxin; Li, Congmei; Yang, Zhiyuan; et al. (Frontiers in Plant Science, 2024)
Aims] This study evaluated the impact of wheat straw return and microbial agent application on rice field environments. [Methods] Using Rice variety Chuankangyou 2115 and a microbial mix of Bacillus subtilis and Trichoderma harzianum. Five treatments were tested: T1 (no straw return), T2 (straw return), T3, T4, and T5 (straw return with varying ratios of Bacillus subtilis and Trichoderma harzianum). [Results] Results indicated significant improvements in rice root length, surface area, dry weight, soil nutrients, and enzyme activity across T2-T5 compared to T1, enhancing yield by 3.81-26.63%. T3 (50:50 microbial ratio) was optimal, further increasing root dry weight, soil enzyme activity, effective panicle and spikelet numbers, and yield. Dominant bacteria in T3 included MBNT15, Defluviicoccus, Rokubacteriales, and Latescibacterota. Higher Trichoderma harzianum proportions (75% in T5) increased straw decomposition but slightly inhibited root growth. Correlation analysis revealed a significant positive relationship between yield and soil microorganisms like Gemmatimonadota and Firmicutes at the heading stage. Factors like dry root weight, straw decomposition rate post-jointing stage, and elevated soil enzyme activity and nutrient content from tiller to jointing stage contributed to increased panicle and spikelet numbers, boosting yield.[Conclusions] The optimal Bacillus subtilis and Trichoderma harzianum ratio for straw return was 50:50, effectively improving soil health and synergizing high rice yield with efficient straw utilization.